2000
DOI: 10.1121/1.429596
|View full text |Cite
|
Sign up to set email alerts
|

From a profiled diffuser to an optimized absorber

Abstract: The quadratic residue diffuser was originally designed for enhanced scattering. Subsequently, however, it has been found that these diffusers can also be designed to produce exceptional absorption. This paper looks into the absorption mechanism of the one-dimensional quadratic residue diffuser. A theory for enhanced absorption is presented. Corresponding experiments have also been done to verify the theory. The usefulness of a resistive layer at the well openings has been verified. A numerical optimization was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 3 publications
(1 reference statement)
0
43
0
Order By: Relevance
“…It should be reminded that viscous and thermal loses were ignored in the calculation of the QRD admittance. For very small well widths, these effects could be significant and introduce larger impedance as well as significant absorption [11,12].…”
Section: Barrier Configurations With Different Qrd Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be reminded that viscous and thermal loses were ignored in the calculation of the QRD admittance. For very small well widths, these effects could be significant and introduce larger impedance as well as significant absorption [11,12].…”
Section: Barrier Configurations With Different Qrd Designsmentioning
confidence: 99%
“…It should also be noted that the QRDs used in the investigation are nonabsorptive. It will be an interesting further work to investigate if an absorptive QRD, as suggested in References [11,12], can further improve the performance of a QRD barrier.…”
Section: F Broad Band Insertion Lossmentioning
confidence: 99%
“…Fujiwara (Fujiwara, Furuta, 1991) installed an absorber on the barrier edge and stated that because the absorber reduces the sound pressure on the edge, the barrier efficiency has been improved. Another study (Wu et al, 2000) has also shown that the variable depth sequence concept can be used to improve significantly the absorption and impedance characteristics of conventional constant depth design.…”
Section: Absorption By Qrd and Prdmentioning
confidence: 99%
“…According to Wu's assumption (Wu, 2000), textile cover is purely resistive, so the reactance part of z is x = 0. For the textile cover used in the measurements, m = 0.15 kg/m 2 .…”
Section: Absorption Of a Resistive Layer Above A Rigid Platementioning
confidence: 99%
“…He was also the first to calculate and measure the influence of resistive layers situated on the entrances of the wells on the absorption coefficient. Based on his approach, Wu et al (2000) pointed out the possibility of creating a highly absorptive structure that would combine the QRD and a resistive covering.…”
Section: Introductionmentioning
confidence: 99%